2012
DOI: 10.1186/1472-6963-12-464
|View full text |Cite
|
Sign up to set email alerts
|

Association between value-based purchasing score and hospital characteristics

Abstract: BackgroundMedicare hospital Value-based purchasing (VBP) program that links Medicare payments to quality of care will become effective from 2013. It is unclear whether specific hospital characteristics are associated with a hospital’s VBP score, and consequently incentive payments.The objective of the study was to assess the association of hospital characteristics with (i) the mean VBP score, and (ii) specific percentiles of the VBP score distribution. The secondary objective was to quantify the associations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 18 publications
2
35
0
3
Order By: Relevance
“…This study agrees with previous work in other disciplines that patient satisfaction scores are affected by non-modifiable patient and system factors, such as the age of the patient or the size of the hospital (8, 9). In a cohort of gynecologic oncology patients in an outpatient setting, we found that patient satisfaction scores are associated with non-modifiable demographic, financial and geographic factors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study agrees with previous work in other disciplines that patient satisfaction scores are affected by non-modifiable patient and system factors, such as the age of the patient or the size of the hospital (8, 9). In a cohort of gynecologic oncology patients in an outpatient setting, we found that patient satisfaction scores are associated with non-modifiable demographic, financial and geographic factors.…”
Section: Discussionsupporting
confidence: 92%
“…Other studies have found lower satisfaction scores for patients who are non-English speakers (8). At the systems level, lower patient satisfaction scores have been observed for densely populated urban areas, hospitals with more beds and those that are non-profit or academic (8, 9). The consistent variation of patient satisfaction by non-modifiable factors suggests that patient satisfaction may be measuring factors beyond just the quality of healthcare delivered.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have suggested that large, urban, teaching, and not-for-profit hospitals were disadvantaged based on their hospital characteristics and patient features 1012 . Under the current CMS reimbursement methodologies, these institutions are more likely to receive financial penalties 8 .…”
Section: Discussionmentioning
confidence: 99%
“…HVBP portends significant economic consequences for the majority of hospitals that rely heavily on Medicare and Medicaid reimbursement as most hospitals have large revenues but low profit margins 11 . Higher HVBP scores are associated with for profit status, smaller size, and location in certain areas of the U.S. 12 . Jha et al 6 described HCAHPS scores regional geographic variability but concluded that poor satisfaction was due to poor quality.…”
Section: Introductionmentioning
confidence: 96%
“…The HVBP is computed using the following four dimensions (9,18,34,37,47,48): -Efficiency (E) In the US model of HVBP, the weights of the HVBP dimensions are expressed in terms of TPS (4,18,37,48). TPS in VBP is calculated based on four dimensions including quality of clinical care 20%, patient experience 30%, outcome 30%, and efficiency 20% of TPS in 2016 -2017 (18,37,(48)(49)(50):…”
Section: Discussionmentioning
confidence: 99%